Autophagy in PDGFRA+ mesenchymal cells is required for intestinal homeostasis and mammalian survival. Issue 2 (1st February 2023) - Yang, Yang; White, Eileen
ABSTRACT: Macroautophagy/autophagy defects are a risk factor for inflamatory bowel disease (IBD), but the mechanism remains unclear. We previously demonstrated that conditional whole-body deletion of the essential Atg7 (autophagy related 7) gene in adult mice ( atg7 Δ/Δ ) causes specific tissue damage and shortens lifespan to three months primarily due to neurodegeneration with surprisingly no disturbing effects on the intestine. In contrast, we recently found that conditional whole-body deletion of other essential autophagy genes, Atg5 or Rb1cc1/Fip200 ( atg5 Δ/Δ or rb1cc1 Δ/Δ ), cause death within five days due to rapid inhibition of autophagy, elimination of intestinal stem cells, and loss of barrier function in the ileum. atg5 Δ/Δ mice lose PDGFRA/PDGFRα + mesenchymal cells (PMCs) and WNT signaling essential for stem cell renewal. Depletion of aspartate and nucleotides in atg5 Δ/Δ ileum was revealed by novel mass-spectrometry imaging (MALDI-MSI), consistent with metabolic insufficiency underlying PMCs loss. The difference in the autophagy gene knockout phenotypes is likely due to distinct kinetics of autophagy loss because gradual whole-body atg5 deletion extends lifespan, phenocopying deletion of Atg7 or Atg12 . Therefore, we established that autophagy is required for ileum PMC metabolism, stem cell maintenance and mammalian survival. PMC loss caused by autophagy deficiency may therefore contribute to IBD.